2015
DOI: 10.4168/aair.2015.7.6.538
|View full text |Cite
|
Sign up to set email alerts
|

Is Folate Status a Risk Factor for Asthma or Other Allergic Diseases?

Abstract: PurposeIt is controversial whether folate status is a risk factor for the development of asthma or other allergic diseases. This study was conducted to investigate whether indirect or direct exposure to folate and impaired folate metabolism, reflected as methylene-tetrahydrofolate reductase (MTHFR) C677T polymorphism, would contribute to the development of asthma and other allergic diseases.MethodsElectronic databases were searched to identify all studies assessing the association between folate status and ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 43 publications
0
37
0
1
Order By: Relevance
“…This study was carried out in OVID by searching databases, including MEDLINE (1946 to February week 2, 2018), EMBASE (1974 to 16 February 2018) and Cochrane Central Register of Controlled Trials (CENTRAL) (January 2018). Medical Subject Headings (MeSH) was used to construct the search terms, together with keywords from related literature . The databases were conducted by search strategy related to fast foods, asthma/wheeze and allergic diseases and the search criteria can be found in Appendix S1 in Supplementary Information.…”
Section: Methodsmentioning
confidence: 99%
“…This study was carried out in OVID by searching databases, including MEDLINE (1946 to February week 2, 2018), EMBASE (1974 to 16 February 2018) and Cochrane Central Register of Controlled Trials (CENTRAL) (January 2018). Medical Subject Headings (MeSH) was used to construct the search terms, together with keywords from related literature . The databases were conducted by search strategy related to fast foods, asthma/wheeze and allergic diseases and the search criteria can be found in Appendix S1 in Supplementary Information.…”
Section: Methodsmentioning
confidence: 99%
“…This literature has been summarized, in several reviews, as conflicting, with limitations caused by heterogeneity in classification of folate intake, the time periods considered for exposure and disease development, and outcome definitions (5)(6)(7)(8). Two more recent studies reported associations between asthma in children older than 4 years of age and the use of folic acid supplements containing 1,000 mg or more during pregnancy (9,10).…”
mentioning
confidence: 99%
“…The review of maternal folate supplementation and allergic disease by Wang et al . assessed four case–control or cohort AE studies.…”
Section: Maternal Folate Supplementationmentioning
confidence: 99%
“…The association between body mass index (BMI) and AE was examined in 30 heterogeneous, mostly cross‐sectional, studies of variable quality . High BMI was associated with a small increased risk of AE in North American (OR = 1.53, 95% CI 1.24–1.89) and Asian populations (OR = 1.3, 95% CI 1.14–1.48), but not European populations (OR 1.01, 95% CI 0.8–1.28).…”
Section: Obesitymentioning
confidence: 99%
See 1 more Smart Citation